Semantyka kognitywna konceptu „kłamstwo” we współczesnym języku rosyjskim - Małecki, Łukasz (Studia Rossica Posnaniensia, 2016)
“Lying” in human consciousness takes the form of a concept — a mental form described by means of such features as traditions, customs, special stereotypes of thinking, behavior models, etc. This article attempts to analyze the linguistic realization of the concept of a “lie” in the Russian language. This language analysis is based on the purposes of cognitive definition.